2016
DOI: 10.3847/0004-637x/817/2/114
|View full text |Cite
|
Sign up to set email alerts
|

A LUMINOUS PECULIAR TYPE IA SUPERNOVA SN 2011HR: MORE LIKE SN 1991T OR SN 2007if?

Abstract: Photometric and spectroscopic observations of a slowly declining, luminous Type Ia supernova (SN Ia) SN 2011hr in the starburst galaxy NGC 2691 are presented. SN 2011hr is found to peak at M B = −19.84 ± 0.40 mag, with a post-maximum decline rate ∆m 15 (B) = 0.92 ± 0.03 mag. From the maximum-light bolometric luminosity, L = (2.30 ± 0.90) × 10 43 erg s −1 , we estimate the mass of synthesized 56 Ni in SN 2011hr to be M ( 56 Ni) = 1.11 ± 0.43 M . SN 2011hr appears more luminous than SN 1991T at around maximum li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 96 publications
(95 reference statements)
1
18
0
Order By: Relevance
“…While luminous SN 1991T-like SNe (Filippenko et al 1992a;Phillips et al 1992) may just be a "more efficient" extension of normal SNe Ia (Mazzali et al 1995;Sasdelli et al 2014;Zhang et al 2016), at the low end of the SN Ia luminosity distribution different mechanisms may be operating. SN 1991bg (Filippenko et al 1992b;Leibundgut et al 1993), the prototypical "fast decliner", and the class which takes its name, which is characterised by spectra showing lines of low-excitation ions (Mazzali et al 1997), have been suggested to be the product of a merger of two WDs below the Chandrasekhar mass (Mazzali & Hachinger 2012;Pakmor et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While luminous SN 1991T-like SNe (Filippenko et al 1992a;Phillips et al 1992) may just be a "more efficient" extension of normal SNe Ia (Mazzali et al 1995;Sasdelli et al 2014;Zhang et al 2016), at the low end of the SN Ia luminosity distribution different mechanisms may be operating. SN 1991bg (Filippenko et al 1992b;Leibundgut et al 1993), the prototypical "fast decliner", and the class which takes its name, which is characterised by spectra showing lines of low-excitation ions (Mazzali et al 1997), have been suggested to be the product of a merger of two WDs below the Chandrasekhar mass (Mazzali & Hachinger 2012;Pakmor et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been accepted that SNe Ia arise from thermonuclear runaway explosions of carbon-oxygen white dwarfs (CO WDs) in binaries, although their progenitor systems and explosion mechanisms are still under debate (see, e.g. Podsiadlowski et al 2008;Hillebrandt et al 2013;Höflich et al 2013;Wang et al 2013;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The spectroscopic criteria eliminate the peculiar SN 2006bt, as it contains Ti ii features. Note that using spectra alone can lead to misleading results, such as those of SN 2011hr (Zhang et al 2016) and LSQ12gdj (Scalzo et al 2014). Note that CSS140126 is a border-line case between a 1991T-like and a 2003fg-like SNe, it has only one low S/N optical spectrum which is featureless, a primary i-band maximum which peaks after that of B band, but displays a secondary i-band maximum.…”
Section: Sample Characteristicsmentioning
confidence: 99%